Competitiveness of Three Beach Destinations in Bali: A MANOVA-Based Comparison - Ida Bagus Gede Agung Widana; Anom Hery Suasapha; I Wayan Sukma Winarya Prabawa; Ni Made Tirtawati (Centre of Excellence in Tourism Udayana University, 2026)
Despite Bali’s millennia-long history of tourism development, understanding the competitiveness of its beach tourism destinations remains limited. Moreover, the island’s relatively small size has led many beach destinations to be located in close proximity to one another, offering similar attractions, activities, and management practices, which may blur their differentiation. This study aims to compare the competitiveness of three closely located beach tourism destinations—Pandawa Beach, Melasti Beach, and Uluwatu Beach—to examine whether significant differences exist among them. It also investigates whether the influence of the indicators used to measure tourism competitiveness differs across these destinations. Adopting a quantitative approach, data were collected from 258 international tourists using a validated self-administered questionnaire. Descriptive statistics were used to profile respondents and to reveal their perceived competitiveness for each destination, while multivariate analysis of variance (MANOVA) was conducted to compare the effects of competitiveness indicators across the three destinations. The findings reveal significant differences in overall competitiveness among the three destinations, with Melasti Beach outperforming Pandawa and Uluwatu across most indicators. The results also indicate that certain competitiveness indicators exert varying effects on overall competitiveness across the destinations, while others show no significant influence. These findings suggest that even geographically proximate beach destinations can exhibit distinct competitiveness profiles. The study concludes with implications for destination management and offers recommendations for enhancing the competitiveness of beach tourism destinations in Bali. This study contributes to the limited empirical understanding of micro-level destination competitiveness in spatially concentrated tourism settings.